Study of the Proton Irradiation Effects in n-FZ DSSD for the Si Tracker at R3B Experiment. Issue 1 (1st February 2022) - Chatterjee, Puspita; Saini, Nitu; Patyal, Shilpa; Kaur, Balwinder; Michael, Thresia; Raheja, Sonia; Srivastava, Ajay K.
Abstract: The R3B collaboration aims to assemble an experimental setup with high resolution and efficiency to perform kinematically complete measurements of reactions with high-energy RIBs (radioactive ion beams). In the R3B experimental setup, the silicon tracker is positioned closest to the target region and can provide high-resolution position measurements of light-charged particles like protons. The three layers of the silicon tracker are constructed with a total of 30 Si double-sidedstrip detectors (DSSD). In this paper, as an option of 23 MeV proton irradiated n-type Float-Zone(Fz)Si double-sidedstrip detector (DSSD) havebeen considered, and by taking the two-trapproton irradiation damage model, the bulk damage effect and the macroscopic performance of the Sidouble-sidedstrip detector (DSSD) have been discussed. The detector is irradiated with three values of proton fluences (equivalent to 1Mev neutron fluence): 2×10 14, 5×10 14 and 8×10 14 cm -2 . By using the Shockley-Read-Hall recombination (SRH) formulation, the full depletion voltage and leakage current have been measured as a function of the irradiation dose, finally the device and process parameters and specifications for the Si double-sidedstrip detector (DSSD) used in the R3B silicon tracker experimenthavebeen proposed.